PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN NASABAH (CUSTOMER EXPERIENCE) DI BANK BUMN KANTOR CABANG MIKRO AREA SAMARINDA - Rosy Widyaningrum; Masjaya Masjaya; Muhammad Noor (Jurnal Paradigma (JP), 2021)
This study aims to analyze and determine the effect of service quality on customer satisfaction at Bank Mandiri Branch Office Micro Unit Palaran. The sample in this study were 92 customers of Mandiri Branch Office Micro Palaran Unit who were randomly assigned using a purposive sampling technique and then analyzed the data obtained using quantitative data analysis. The results showed that there is a significant influence between service quality on customer satisfaction of service users of Bank Mandiri Mikro Unit Palaran. The influence of service quality variables on customer satisfaction at Bank Mandiri Mikro Unit Palaran is negative. This means that the higher and better the quality of service provided by Bank Mandiri Mikro Unit Palaran, the higher customer satisfaction, and customers are less satisfied with the quality of service provided by frontline staff or Bank officers.Keywords: Service Quality, Customer Satisfaction